Implicit change leadership schemas, perceived effective change management, and teachers’ commitment to change in secondary schools in the Philippines - Guerrero, Joyce M (Archīum Ateneo, 2018)
Implicit change leadership theory (ICLT) highlights the importance of determining congruence between the ideal and actual change leadership schemas of employees in successful change management. This paper utilized ICLT in exploring effective change leadership and management in secondary schools and examined how these influence teachers’ commitment to change. Data were gathered from 707 secondary school teachers from both private and public high schools in the Philippines. Findings indicated that (1) teachers seem to have a more holistic and integrative view of change leadership schemas than employees of business organizations, (2) teachers’ change leadership schemas significantly predicts perceived effectiveness of change management, and teachers’ affective commitment to change, and (3) perceived effectiveness of change management significantly mediates the effect of change leadership schemas on teachers’ affective commitment to change. This study expanded the applicability of ICLT in basic education settings and contributes to the understanding of effective change leadership and change management in schools. Implications on practice and further recommendations for school leaders are also discussed.